1999
DOI: 10.1136/thx.54.8.681
|View full text |Cite
|
Sign up to set email alerts
|

Objectives, methods and content of patient education programmes for adults with asthma: systematic review of studies published between 1979 and 1998

Abstract: Background-Education programmes for adults with asthma vary widely. Such variability suggests a lack of consensus on what works and what does not. The objectives of this paper are to describe asthma education programmes and assess their variability. Methods-A systematic review of reports published between 1979 and 1998 was conducted. Medline, the CINAHL database, the PsycINFO database, the Cochrane collaboration database, the Dissertation Index database, and cross referencing were used to identify educational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 76 publications
0
34
0
2
Order By: Relevance
“…67,72,[92][93]108,111 High-quality reviews of similar interventions for children suggest more mixed results. 73,92,93,104 Evidence on the optimal form and methods for delivery of selfmanagement education, 72,98,104,107,109,111 other types of psycho-educational programmes (e.g. psychotherapeutic approaches) 96,97,103,106,112 and multifaceted interventions 92,115,120 appears to be more sparse and a number of these areas have been identified for further research or consideration in ongoing Cochrane reviews.…”
Section: Psycho-educational Interventions In Difficult Asthma: Contexmentioning
confidence: 99%
See 2 more Smart Citations
“…67,72,[92][93]108,111 High-quality reviews of similar interventions for children suggest more mixed results. 73,92,93,104 Evidence on the optimal form and methods for delivery of selfmanagement education, 72,98,104,107,109,111 other types of psycho-educational programmes (e.g. psychotherapeutic approaches) 96,97,103,106,112 and multifaceted interventions 92,115,120 appears to be more sparse and a number of these areas have been identified for further research or consideration in ongoing Cochrane reviews.…”
Section: Psycho-educational Interventions In Difficult Asthma: Contexmentioning
confidence: 99%
“…Results of studies were tabulated and all but three studies showed positive effects on at least one outcome at one or more time points; however, no attempt was made to synthesise results qualitatively or quantitatively. A systematic review of patient education programmes for adults with asthma 109 summarised details of the content and methods applied in, but not results from, 94 studies of such programmes and concluded that interventions were generally poorly described and reported.…”
Section: Psycho-educational Interventions In Adults With Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…In two recent reviews it was found that asthma education programmes (with or without guidelines for self-treatment of exacerbations) vary widely in their methods and content [36,37]. This makes it difficult to identify the most effective components of these programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Written personalised asthma action plans (PAAPs) can be introduced as part of a structured educational discussion with a trained asthma healthcare professional. 43 Key components of an asthma educational programme 44 are shown in Box 5, and the components of a written PAAP 45 are shown in Box 6.…”
Section: Loss Of Asthma Control Asthma Action Plans and Self Managementmentioning
confidence: 99%